2005
DOI: 10.1177/070674370505000704
|View full text |Cite
|
Sign up to set email alerts
|

SCL-90-R and 16PF Profiles of Senior High School Students with Excessive Internet Use

Abstract: Objective: To investigate the psychiatric symptomatology and personality characteristics of Korean senior high school students considered to use the Internet to excess. Method: We administered a questionnaire packet to students that included 4 measures. These measures included a questionnaire on Internet use patterns during the previous month, the Internet Addiction Test (IAT), the Symptom Checklist-90-R (SCL-90-R), and the Sixteen Personality Factor Questionnaire (16PF). A total of 328 students, aged 15 to 19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
113
1
24

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 199 publications
(149 citation statements)
references
References 11 publications
11
113
1
24
Order By: Relevance
“…Yang et al noted that excessive Internet use according to the Y-IAT was associated with higher levels of psychiatric symptoms on the Symptom Checklist-90-Revision in Korea. 21,45 Additionally, Yen et al also reported that adolescents with Internet addiction had more ADHD symptoms and more severe depression. 46 Although the concept of and criteria for Internet addiction remain controversial, four components are considered essential: (a) excessive use, often with a loss of sense of time or neglect of basic drives; (b) withdrawal, including feelings of anger, tension, and/or depression and anxiety when the Internet is inaccessible; (c) obsession, including a constant need for better computer equipment, more software, or more hours of use; and (d) negative consequences, including arguments, lying, poor achievement, social isolation, and fatigue.…”
Section: Discussionmentioning
confidence: 99%
“…Yang et al noted that excessive Internet use according to the Y-IAT was associated with higher levels of psychiatric symptoms on the Symptom Checklist-90-Revision in Korea. 21,45 Additionally, Yen et al also reported that adolescents with Internet addiction had more ADHD symptoms and more severe depression. 46 Although the concept of and criteria for Internet addiction remain controversial, four components are considered essential: (a) excessive use, often with a loss of sense of time or neglect of basic drives; (b) withdrawal, including feelings of anger, tension, and/or depression and anxiety when the Internet is inaccessible; (c) obsession, including a constant need for better computer equipment, more software, or more hours of use; and (d) negative consequences, including arguments, lying, poor achievement, social isolation, and fatigue.…”
Section: Discussionmentioning
confidence: 99%
“…Among a sample of adults (median age of 20 years), higher levels of computer usage were associated with both lower physical activity levels and perception of computer usage as a barrier to physical activity (24). Moreover, Morgan and Cotton, and Yang et al suggested that excessive use of the Internet caused students to deviate from the real life and fail to cope with difficulties they encounter (25,26). Participants of a study conducted by Rotunda et al reported certain negative outcomes of Internet usage and that problematic practices, which were less prevalent, became more common (27).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly studies of young adult samples indicate that self-reported loneliness is positively correlated with the rate of Internet use (Engelberg & Sjoberg, 2004;Nichols & Nicki, 2005), and individuals who report excessive Internet use are characterized by an elevated rate of psychiatric disorders (Blacket al, 1999;Shapira, et al, 2001;Shapira et al, 2003;Yoo et al, 2004). A recent study of normal high school students revealed that heavy Internet use was associated with heightened psychiatric symptoms on self report measures (Yang et al, 2005).…”
Section: Introductionmentioning
confidence: 97%